READING OF GOSTLY APPEARANCES WITH A REVELATION VIEW IN SHAKESPEARE’S HAMLET AND MACBETH - SOEDE, Casimir Comlan; YEKINI, IBRAHIM (My University, 2018)
Abstract The use Shakespeare makes of the supernatural in Hamlet and Macbeth as far as ghosts and witches are concerned shows how the author exploits the cultural heritage of the country; the beliefs and the superstitions of the Elizabethan era. In Hamlet and Macbeth, the ghosts are used as catalysts in the sense that the supernatural is always placed in the closest relation with the main characters. L’utilisation que Shakespeare fait du surnaturel dans Hamlet et Macbeth s’agissant des fantômes et sorcières montre comment il exploite le patrimoine culturel de son pays. Dans le cas présent, il s’agit de croyances et de superstitions de l’époque élisabéthaine. Dans Hamlet et Macbeth, les fantômes servent de catalyseurs dans la mesure où le surnaturel a une intime relation avec le caractère des principaux personnages.
Keywords: Mots clés : fantômes; surnaturel; sorcières; apparition; Keywords: Ghosts; supernatural; witches; appearance.